Optimism and Psychological Distress Among First-Year Students During The COVID-19 Pandemic - Rodiyah, Rodiyah (Faculty of Psychology, Diponegoro University, 2021)
The Covid-19 pandemic has had a global effect, causing psychological distress for many people. This researchaims to determine the relationship between optimism and psychological distress among first-year students duringthe Covid-19 pandemic. This research performed using the quantitative method with non-probability samplingapplied with a quota sampling technique and obtained a sample of 100 first-year students at Universitas HangTuah (UHT). Optimism was measured using Life Orientation Test-Revised (LOT-R) developed by Scheier,Carver, and Bridges. Psychological distress was measured by the Kessler Psychological Distress Scale (K10)developed by Kessler and Mroczek. The results of the data analysis using Spearman Rank-order showed acorrelation coefficient (rs) of -.395 with a value of p = .000 (p < .01). This demonstrates that there is a negativerelationship between optimism and psychological distress among first-year students during the Covid-19pandemic. The results also reveal that the majority in the level of optimism and psychological distress amongfirst-year students of UHT is in the high category.